A method for preparing selenium-doped cobalt ditelluride electrode material
Through the preparation of selenium-doped cobalt ditelluride electrode material, the problems of polarization and slow kinetics of CoTe2 during charging and discharging are solved, and the electrode material performance of sodium ion batteries is significantly improved, achieving higher sodium storage capacity and Cyclic stability.
Patent Information
- Application Number
- CN202211491567.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-11-25
- Publication Date
- 2024-12-20
- Estimated Expiration
- 2042-11-25
AI Technical Summary
CoTe2 has a large polarization and kinetic slowness during charging and discharging, which conceals its excellent rate performance and long cycle stability, resulting in limited application in sodium ion batteries.
The preparation method of selenium-doped cobalt ditelluride electrode material includes the synthesis of ZIF-67, the preparation of CoTe2 and CoTe2-xSex, and then mixing with super p and CMCNa in deionized water to form a slurry and uniformly on the copper foil Dry after application to form an efficient working electrode.
The charge and discharge capacity and reaction kinetics of the electrode material are significantly improved, the rate performance and cycling stability are improved, and the discharge capacity of the first round of the CoTe2-xSex material is increased from 427mAh/g to 592mAh/g at a current density of 0.05A/g.
Smart Images

Figure CN115893329B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of sodium ion batteries, and in particular relates to a method for preparing a selenium-doped cobalt ditelluride electrode material. Background Art
[0002] In recent decades, there has been a great deal of interest in developing high-performance secondary batteries for energy storage systems such as electric vehicles, hybrid electric vehicles, and portable electronic devices, driven by the desire to create alternatives to unsustainable fossil fuels. Rechargeable lithium-ion batteries are a representative energy storage system because of their ability to produce high energy density and power. However, conventional graphite anodes for lithium-ion batteries have slow rate capabilities, with a theoretical capacity of 372 mA hg -1 . Currently reported materials that can form lithium alloys include Si, Sn, Ge, P, Sb, etc. Since they can form a variety of lithium-ion alloys, they are considered to be candidate anode materials for high-capacity lithium-ion batteries. However, during repeated insertion / extraction processes, these materials suffer from inevitable capacity decay due to large changes in volume.
[0003] Sodium-ion batteries are considered to be the next generation energy storage system to replace rechargeable lithium-ion batteries due to their natural abundance, environmental benignity, and low sodium resource price. In addition, the electrochemical redox potential and electrochemical reaction mechanism of sodium-ion batteries are the same as those of lithium-ion batteries. Most of the anode materials studied in lithium-ion batteries are candidate materials for sodium-ion batteries. So far, various metal chalcogenides, phosphides, and nitrides have been explored as anode materials in sodium-ion batteries. However, due to the low cost of Na + The larger ionic radius often leads to poor diffusion kinetics of electrode materials in practical applications. + The poor diffusion coefficient and huge volume expansion of the anode materials with ideal sodium storage performance are still limited. In the past few decades, carbon materials (such as soft carbon, hard carbon, graphite, graphene, etc.) have been widely used due to their large interlayer spacing, high conductivity, and favorable Na + The transport of ions and other characteristics have been systematically studied. However, their low volumetric capacity and the risk of sodium plating on low-voltage platforms (<0.2V) limit the overall energy density and increase safety risks. Therefore, the development of a suitable anode material with high capacity and long cycle stability remains one of the main challenges in the development of sodium-ion batteries.
[0004] It is well known that alloying and conversion materials involving multi-electron transfer have higher theoretical capacity than intercalation carbon materials. However, alloy-type anode materials have inherently large volume changes, resulting in severe electrode crushing and poor cycle stability. Conversion-type anode materials (such as transition metal sulfide compounds) have been widely studied due to their abundant reserves, wide diversity, and high theoretical specific capacity. From the perspective of electrochemical reactions, transition metal sulfide compounds have weaker MS bonds, which are more conducive to the participation of multiple electrons in the conversion reaction of sodium-ion batteries, which means that the material has a higher theoretical upper limit. Among transition metal sulfide materials, sulfides and selenides have been widely studied in sodium-ion batteries. However, these materials have disadvantages such as weak conductivity, slow kinetics, and. Among various chalcogenides, transition metal tellurides have higher electronic conductivity and density than sulfides and selenides, so higher rate performance and volumetric specific capacity can be obtained. In addition, the larger Te atomic ion radius can produce more deformation areas of the buffer material, while the weaker metal bond is more conducive to Na + More importantly, the discharge product (sodium telluride) is much more stable in conventional electrolytes than Na x S and Na x Se has higher chemical stability, which contributes to more stable electrochemical performance. In view of these advantages, transition metal tellurides have been gradually applied to sodium ion batteries. 2 Has a higher density (7.92gcm -3 ), the discharge product of metal Co has higher conductivity. Based on the above advantages, CoTe 2 It can be expected to become a potential anode for sodium-ion batteries.
[0005] Among transition metal tellurides (TMTes), CoTe 2 Due to its unique physical and chemical properties, it has attracted extensive attention and research, especially in energy conversion systems. In addition, compared with other common tellurium-based electrode materials (SnTe, ZnTe, Sb 2 Te 3 ) compared to CoTe 2 With a higher density, it is beneficial to obtain a higher volume energy density in the field of energy storage. However, like most metal tellurides, CoTe 2 The disadvantages of large polarization and sluggish kinetics during charge and discharge obscures its excellent rate performance and long cycle stability. In order to solve these key problems, many strategies have been proposed to improve CoTe 2 Cycling stability and rate characteristics of the anode. For example, the synthesis of conductive matrix (e.g., CoTe 2 -C microspheres, CoTe 2Nanorods / reduced graphene oxide, CoTe 2 / G nanosheets, etc.), and build strong nanostructures (e.g., polyhedral CoTe 2 -C and MOF-derived CoTe 2 @NPC). Combining with porous carbon materials can synergistically buffer volume expansion, alleviate agglomeration problems, reduce polarization, and thus improve reaction kinetics. In addition, nanoparticles in the form of nanostructures can significantly reduce the mechanical stress during the insertion and extraction of sodium ions, effectively alleviating the problem of electrode material crushing. Summary of the invention
[0006] The purpose of the present invention is to provide a method for preparing a selenium-doped cobalt ditelluride electrode material, which is intended to solve the problem of CoTe 2 It has disadvantages such as large polarization and kinetic sluggishness during the charge and discharge process, which obscures its excellent rate performance and long-cycle stability.
[0007] The present invention is achieved by a method for preparing a selenium-doped cobalt ditelluride electrode material, comprising the following preparation steps:
[0008] Step 1: Take Co(NO) 3 6H 2 O, methanol, 2-methylimidazole and anhydrous ethanol to synthesize ZIF-67;
[0009] Step 2: Prepare CoTe from ZIF-67 powder and Te powder 2 ;
[0010] Step 3: Take CoTe 2 Preparation of CoTe from powder and Se powder 2-x Se x ;
[0011] Step 4: Take CoTe 2-x Se x , super p and CMCNa are mixed in deionized water to form a slurry;
[0012] Step 5: Apply the slurry evenly on a copper foil with a diameter of 1.2 cm;
[0013] Step 6: Place the copper foil coated with the slurry in step 5 in a vacuum drying oven and dry for 10 hours to prepare a working electrode. The mass of the active material is about 0.8 mg.
[0014] Further technical scheme, the specific steps of synthesizing ZIF-67 in step 1 are as follows:
[0015] 1) Take 230-270 mg of Co(NO) 3 6H 2O was added into 25 ml of methanol and stirred evenly to prepare solution A;
[0016] 2) Add 310-350 mg of 2-methylimidazole to 25 ml of methanol and stir evenly to prepare solution B;
[0017] 3) Pour the above solution B into solution A and mix well to obtain solution C;
[0018] 4) leaving solution C at room temperature for 24 hours;
[0019] 5) Centrifuge the static solution C three times with anhydrous ethanol;
[0020] 6) Dry the product obtained by centrifugation at 80°C for 12 h to obtain ZIF-67.
[0021] Further technical scheme, the specific steps of synthesizing ZIF-67 in step 1 are as follows:
[0022] 1) Take 249 mg of Co(NO) 3 6H 2 O was added into 25 ml of methanol and stirred evenly to prepare solution A;
[0023] 2) 328 mg of 2-methylimidazole was added to 25 ml of methanol and stirred to obtain solution B;
[0024] 3) Pour the above solution B into solution A and mix well to obtain solution C;
[0025] 4) leaving solution C at room temperature for 24 hours;
[0026] 5) Centrifuge the static solution C three times with anhydrous ethanol;
[0027] 6) Dry the product obtained by centrifugation at 80°C for 12 h to obtain ZIF-67.
[0028] In a further technical solution, in step 2, CoTe is prepared 2 The specific steps are as follows:
[0029] 1) Take 25-35 mg ZIF-67 powder and 110-130 mg Te powder and place them in two magnetic boats respectively;
[0030] 2) Place the magnetic boat in a tube furnace, introduce argon, heat to 600°C at a rate of 3°C / min, keep warm for 4 hours, cool to room temperature and take out. The black powder obtained is CoTe 2 .
[0031] In a further technical solution, in step 2, CoTe is prepared2 The specific steps are as follows:
[0032] 1) Take 30 mg ZIF-67 powder and 120 mg Te powder and place them in two magnetic boats respectively;
[0033] 2) Place the magnetic boat in a tube furnace, introduce argon, heat to 600°C at a rate of 3°C / min, keep warm for 4 hours, cool to room temperature and take out. The black powder obtained is CoTe 2 .
[0034] In a further technical solution, in step 3, CoTe is prepared 2-x Se x The specific steps are as follows:
[0035] 1) Take 25-35 mg CoTe 2 powder and 10-20 mg of Se powder were placed in two magnetic boats;
[0036] 2) Place the magnetic boat in a tube furnace, introduce argon, heat to 550°C at a rate of 3°C / min, keep warm for 2h, cool to room temperature and take out. The obtained black powder is CoTe 2-x Se x .
[0037] In a further technical solution, in step 3, CoTe is prepared 2-x Se x The specific steps are as follows:
[0038] 1) Take 30 mg CoTe 2 powder and 15 mg of Se powder were placed in two magnetic boats;
[0039] 2) Place the magnetic boat in a tube furnace, introduce argon, heat to 550°C at a rate of 3°C / min, keep warm for 2h, cool to room temperature and take out. The obtained black powder is CoTe 2-x Se x .
[0040] In a further technical solution, the ratio of the slurry in step 4 is CoTe 2-x Se x :super p:CMCNa=7:1.5:1.5.
[0041] The present invention provides a method for preparing a selenium-doped cobalt ditelluride electrode material, which 2 After selenization, the charge and discharge capacity of the electrode material is greatly improved. At a current density of 0.05A / g, CoTe 2 The first cycle discharge capacity is only 427mAh / g, while CoTe 2-x Sex The first cycle discharge capacity is increased to 592mAh / g, CoTe 2-x Se x The material has a larger sodium storage capacity. The present invention has a larger sodium storage capacity. 2 Anion substitution is carried out to improve the reaction kinetics, so that the anode material has higher charge and discharge capacity, better rate performance and cycle stability. BRIEF DESCRIPTION OF THE DRAWINGS
[0042] Figure 1 The SEM image of ZIF-67 provided by the embodiment of the present invention;
[0043] Figure 2 CoTe provided in the embodiment of the present invention 2 SEM images of
[0044] Figure 3 CoTe provided in the embodiment of the present invention 2-x Se x SEM images of
[0045] Figure 4 CoTe provided in the embodiment of the present invention 2 With CoTe 2-x Se x Constant current charge and discharge curves of negative electrode materials under different rate conditions. DETAILED DESCRIPTION
[0046] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention.
[0047] The specific implementation of the present invention is described in detail below in conjunction with specific embodiments.
[0048] Embodiment 1
[0049] A method for preparing a selenium-doped cobalt ditelluride electrode material comprises the following preparation steps:
[0050] Step 1: Take Co(NO) 3 6H 2 O, methanol, 2-methylimidazole and anhydrous ethanol to synthesize ZIF-67;
[0051] The specific steps for synthesizing ZIF-67 are as follows:
[0052] 1) Take 230 mg of Co(NO) 3 6H 2 O was added into 25 ml of methanol and stirred evenly to prepare solution A;
[0053] 2) Add 310 mg of 2-methylimidazole to 25 ml of methanol and stir evenly to prepare solution B;
[0054] 3) Pour the above solution B into solution A and mix well to obtain solution C;
[0055] 4) leaving solution C at room temperature for 24 hours;
[0056] 5) Centrifuge the static solution C three times with anhydrous ethanol;
[0057] 6) Dry the product obtained by centrifugation at 80° C. for 12 h to obtain ZIF-67;
[0058] Step 2: Prepare CoTe from ZIF-67 powder and Te powder 2 ;
[0059] Preparation of CoTe 2 The specific steps are as follows:
[0060] 1) Take 25 mg ZIF-67 powder and 110 mg Te powder and place them in two magnetic boats respectively;
[0061] 2) Place the magnetic boat in a tube furnace, introduce argon, heat to 600°C at a rate of 3°C / min, keep warm for 4 hours, cool to room temperature and take out. The black powder obtained is CoTe 2 ;
[0062] Step 3: Take CoTe 2 Preparation of CoTe from powder and Se powder 2-x Se x ;
[0063] Preparation of CoTe 2-x Se x The specific steps are as follows:
[0064] 1) Take 25 mg CoTe 2 powder and 10 mg of Se powder were placed in two magnetic boats;
[0065] 2) Place the magnetic boat in a tube furnace, introduce argon, heat to 550°C at a rate of 3°C / min, keep warm for 2h, cool to room temperature and take out. The black powder obtained is CoTe 2-x Se x ;
[0066] Step 4: Take CoTe 2-x Se x , super p and CMCNa were mixed in deionized water to form a slurry, CoTe 2-x Sex :super p:CMCNa=7:1.5:1.5;
[0067] Step 5: Apply the slurry evenly on a copper foil with a diameter of 1.2 cm;
[0068] Step 6: Place the copper foil coated with the slurry in step 5 in a vacuum drying oven and dry for 10 hours to prepare a working electrode. The mass of the active material is about 0.8 mg.
[0069] Embodiment 2
[0070] A method for preparing a selenium-doped cobalt ditelluride electrode material comprises the following preparation steps:
[0071] Step 1: Take Co(NO) 3 6H 2 O, methanol, 2-methylimidazole and anhydrous ethanol to synthesize ZIF-67;
[0072] The specific steps for synthesizing ZIF-67 are as follows:
[0073] 1) Take 270 mg of Co(NO) 3 6H 2 O was added into 25 ml of methanol and stirred evenly to prepare solution A;
[0074] 2) Add 350 mg of 2-methylimidazole to 25 ml of methanol and stir evenly to prepare solution B;
[0075] 3) Pour the above solution B into solution A and mix well to obtain solution C;
[0076] 4) leaving solution C at room temperature for 24 hours;
[0077] 5) Centrifuge the static solution C three times with anhydrous ethanol;
[0078] 6) Dry the product obtained by centrifugation at 80° C. for 12 h to obtain ZIF-67;
[0079] Step 2: Prepare CoTe from ZIF-67 powder and Te powder 2 ;
[0080] Preparation of CoTe 2 The specific steps are as follows:
[0081] 1) Take 35 mg ZIF-67 powder and 130 mg Te powder and place them in two magnetic boats respectively;
[0082] 2) Place the magnetic boat in a tube furnace, introduce argon, heat to 600°C at a rate of 3°C / min, keep warm for 4 hours, cool to room temperature and take out. The black powder obtained is CoTe 2 ;
[0083] Step 3: Take CoTe 2 Preparation of CoTe from powder and Se powder 2-x Se x ;
[0084] Preparation of CoTe 2-x Se x The specific steps are as follows:
[0085] 1) Take 35 mg CoTe 2 powder and 20 mg of Se powder were placed in two magnetic boats;
[0086] 2) Place the magnetic boat in a tube furnace, introduce argon, heat to 550°C at a rate of 3°C / min, keep warm for 2h, cool to room temperature and take out. The obtained black powder is CoTe 2-x Se x ;
[0087] Step 4: Take CoTe 2-x Se x , super p and CMCNa were mixed in deionized water to form a slurry, CoTe 2-x Se x :super p:CMCNa=7:1.5:1.5;
[0088] Step 5: Apply the slurry evenly on a copper foil with a diameter of 1.2 cm;
[0089] Step 6: Place the copper foil coated with the slurry in step 5 in a vacuum drying oven and dry for 10 hours to prepare a working electrode. The mass of the active material is about 0.8 mg.
[0090] Embodiment 3
[0091] A method for preparing a selenium-doped cobalt ditelluride electrode material comprises the following preparation steps:
[0092] Step 1: Take Co(NO) 3 6H 2 O, methanol, 2-methylimidazole and anhydrous ethanol to synthesize ZIF-67;
[0093] The specific steps for synthesizing ZIF-67 are as follows:
[0094] 1) Take 249 mg of Co(NO) 3 6H 2O was added into 25 ml of methanol and stirred evenly to prepare solution A;
[0095] 2) 328 mg of 2-methylimidazole was added to 25 ml of methanol and stirred to obtain solution B;
[0096] 3) Pour the above solution B into solution A and mix well to obtain solution C;
[0097] 4) leaving solution C at room temperature for 24 hours;
[0098] 5) Centrifuge the static solution C three times with anhydrous ethanol;
[0099] 6) Dry the product obtained by centrifugation at 80°C for 12 h to obtain ZIF-67. The SEM image of ZIF-67 is shown in Figure 1 ;
[0100] Step 2: Prepare CoTe from ZIF-67 powder and Te powder 2 ;
[0101] Preparation of CoTe 2 The specific steps are as follows:
[0102] 1) Take 30 mg ZIF-67 powder and 120 mg Te powder and place them in two magnetic boats respectively;
[0103] 2) Place the magnetic boat in a tube furnace, introduce argon, heat to 600°C at a rate of 3°C / min, keep warm for 4 hours, cool to room temperature and take out. The black powder obtained is CoTe 2 , CoTe 2 See SEM pictures Figure 2 ;
[0104] Step 3: Take CoTe 2 Preparation of CoTe from powder and Se powder 2-x Se x ;
[0105] Preparation of CoTe 2-x Se x The specific steps are as follows:
[0106] 1) Take 30 mg CoTe 2 powder and 15 mg of Se powder were placed in two magnetic boats;
[0107] 2) Place the magnetic boat in a tube furnace, introduce argon, heat to 550°C at a rate of 3°C / min, keep warm for 2h, cool to room temperature and take out. The black powder obtained is CoTe 2-x Se x , CoTe 2-x Sex See SEM pictures Figure 3 ;
[0108] Step 4: Take CoTe 2-x Se x , super p and CMCNa were mixed in deionized water to form a slurry, CoTe 2-x Se x :super p:CMCNa=7:1.5:1.5;
[0109] Step 5: Apply the slurry evenly on a copper foil with a diameter of 1.2 cm;
[0110] Step 6: Place the copper foil coated with the slurry in step 5 in a vacuum drying oven and dry for 10 hours to prepare a working electrode. The mass of the active material is about 0.8 mg.
[0111] Comparative Example 1
[0112] CoTe 2 The method for preparing an electrode material comprises the following steps:
[0113] Step 1: Take Co(NO) 3 6H 2 O, methanol, 2-methylimidazole and anhydrous ethanol to synthesize ZIF-67;
[0114] The specific steps for synthesizing ZIF-67 are as follows:
[0115] 1) Take 249 mg of Co(NO) 3 6H 2 O was added into 25 ml of methanol and stirred evenly to prepare solution A;
[0116] 2) 328 mg of 2-methylimidazole was added to 25 ml of methanol and stirred to obtain solution B;
[0117] 3) Pour the above solution B into solution A and mix well to obtain solution C;
[0118] 4) leaving solution C at room temperature for 24 hours;
[0119] 5) Centrifuge the static solution C three times with anhydrous ethanol;
[0120] 6) Dry the product obtained by centrifugation at 80°C for 12 h to obtain ZIF-67. The SEM image of ZIF-67 is shown in Figure 1 ;
[0121] Step 2: Prepare CoTe from ZIF-67 powder and Te powder 2 ;
[0122] Preparation of CoTe 2 The specific steps are as follows:
[0123] 1) Take 30 mg ZIF-67 powder and 120 mg Te powder and place them in two magnetic boats respectively;
[0124] 2) Place the magnetic boat in a tube furnace, introduce argon, heat to 600°C at a rate of 3°C / min, keep warm for 4 hours, cool to room temperature and take out. The black powder obtained is CoTe 2 , CoTe 2 See SEM pictures Figure 2 ;
[0125] Step 3: Take CoTe 2 , super p and CMCNa were mixed in deionized water to form a slurry, CoTe 2 :super p:CMCNa=7:1.5:1.5;
[0126] Step 4: Apply the slurry evenly on a copper foil with a diameter of 1.2 cm;
[0127] Step 5: Place the copper foil coated with the slurry in step 5 in a vacuum drying oven and dry for 10 hours to prepare a working electrode. The mass of the active material is about 0.8 mg.
[0128] The working electrodes prepared by Example 3 and Comparative Example 1 were respectively assembled into the negative electrode of the sodium ion button half-cell:
[0129] 2032 button cells will be used to determine the electrochemical properties of the electrode materials.
[0130] The parts of the sodium ion button half-cell are: positive electrode shell, working electrode, diaphragm, sodium sheet, gasket, spring sheet, negative electrode shell and electrolyte.
[0131] The button cell was assembled in a glove box filled with argon atmosphere. Sodium metal sheets were used as reference electrodes and counter electrodes, and 1 M NaClO was selected as the electrolyte. 4 / EC:DEC(1:1,v)5%FEC.
[0132] Electrochemical testing of sodium ion batteries
[0133] The battery is charged and discharged within the voltage range of 0.1 to 3.0V. Figure 4 This is a constant current charge and discharge curve of the sodium ion battery negative electrode material under different rate conditions.
[0134] CoTe 2 After selenization, the charge and discharge capacity of the electrode material is greatly improved. At a current density of 0.05A / g, CoTe 2The first cycle discharge capacity is only 427mAh / g, while CoTe 2-x Se x The first cycle discharge capacity is increased to 592mAh / g, CoTe 2-x Se x The material has a greater sodium storage capacity.
[0135] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the present invention.
Claims
1. A method for preparing a selenium-doped cobalt ditelluride electrode material, characterized in that: The method comprises the following preparation steps: Step 1: Take Co(NO)3·6H2O, methanol, 2-methylimidazole and anhydrous ethanol to synthesize ZIF-67; Step 2: Prepare CoTe2 from ZIF-67 powder and Te powder; Step 3: Prepare CoTe2 powder and Se powder 2-x Se x ; Step 4: Take CoTe 2-x Se x , super p and CMCNa are mixed in deionized water to form a slurry; Step 5: Apply the slurry evenly on a copper foil with a diameter of 1.2 cm; Step 6: Place the copper foil coated with the slurry in step 5 in a vacuum drying oven and dry for 10 hours to prepare a working electrode, with the mass of the active material being 0.8 mg; The specific steps of synthesizing ZIF-67 in step 1 are as follows: 1) Add 230-270 mg of Co(NO)3·6H2O to 25 ml of methanol and stir well to prepare solution A; 2) Add 310-350 mg of 2-methylimidazole to 25 ml of methanol and stir evenly to prepare solution B; 3) Pour the above solution B into solution A and mix well to obtain solution C; 4) Let solution C stand at room temperature for 24 hours; 5) Centrifuge the static solution C three times with anhydrous ethanol; 6) Dry the product obtained by centrifugation at 80°C for 12 hours to obtain ZIF-67; In step 3, CoTe is prepared 2-x Se x The specific steps are as follows: 1) Take 25-35 mg CoTe2 powder and 10-20 mg Se powder and place them in two magnetic boats respectively; 2) Place the magnetic boat in a tube furnace, introduce argon, heat to 550℃ at a rate of 3℃ / min, keep warm for 2h, cool to room temperature and take out. The black powder obtained is CoTe 2-x Se x ; The ratio of the slurry in step 4 is CoTe 2-x Se x :super p:CMCNa=7:1.5:1.5; The specific steps of preparing CoTe2 in step 2 are as follows: 1) Take 25-35 mg ZIF-67 powder and 110-130 mg Te powder and place them in two magnetic boats respectively; 2) Place the magnetic boat in a tubular furnace, introduce argon, heat to 600°C at a rate of 3°C / min and keep warm for 4 hours, cool to room temperature and take out. The resulting black powder is CoTe2.
2. The method for preparing the selenium-doped cobalt ditelluride electrode material according to claim 1, characterized in that: The specific steps of synthesizing ZIF-67 in step 1 are as follows: 1) Add 249 mg of Co(NO)3·6H2O to 25 ml of methanol and stir well to prepare solution A; 2) Add 328 mg of 2-methylimidazole to 25 ml of methanol and stir evenly to prepare solution B; 3) Pour the above solution B into solution A and mix well to obtain solution C; 4) Let solution C stand at room temperature for 24 hours; 5) Centrifuge the static solution C three times with anhydrous ethanol; 6) Dry the product obtained by centrifugation at 80°C for 12 h to obtain ZIF-67.
3. The method for preparing the selenium-doped cobalt ditelluride electrode material according to claim 1, characterized in that: The specific steps of preparing CoTe2 in step 2 are as follows: 1) Take 30 mg ZIF-67 powder and 120 mg Te powder and place them in two magnetic boats respectively; 2) Place the magnetic boat in a tubular furnace, introduce argon, heat to 600°C at a rate of 3°C / min and keep warm for 4 hours, cool to room temperature and take out. The resulting black powder is CoTe2.
4. The method for preparing the selenium-doped cobalt ditelluride electrode material according to claim 1, characterized in that: In step 3, CoTe is prepared 2-x Se x The specific steps are as follows: 1) Take 30 mg CoTe2 powder and 15 mg Se powder and place them in two magnetic boats respectively; 2) Place the magnetic boat in a tube furnace, introduce argon, heat to 550℃ at a rate of 3℃ / min, keep warm for 2h, cool to room temperature and take out. The black powder obtained is CoTe 2-x Se x .
